Agricultural production and children's diets: Evidence from rural Ethiopia - Hirvonen, Kalle; Hoddinott, John F. (Wiley, 2017)
We study the relationship between pre‐school children's food consumption and household agricultural production. Using a large household survey from rural Ethiopia, we find that increasing household production diversity leads to considerable improvements in children's dietary diversity. However, we also document how this nonseparability of consumption and production does not hold for households that have access to food markets. These findings imply that nutrition‐sensitive agricultural interventions that push for market integration are likely to be more effective in reducing under‐nutrition than those promoting production diversity.